The National Evaluation of Upward Bound. The Short-Term Impact of Upward Bound An Interim Report - Myers, David E.; Schirm, Allen L.; Mathematica Policy Research, Washington, DC.; Educational Testing Service, Atlanta, GA.; Westat, Inc., Rockville, MD.; Decision Information Resources, Inc., Houston, TX. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This report on the short-term effects of Upward Bound, a federal pre-college program designed to help economically disadvantaged students complete high school and gain access to post-secondary education, presents interim findings from the Longitudinal Effectiveness Study of Upward Bound based on data on approximately 2,800 students during the first year or two of high school. At present, there are more than 600 Upward Bound projects; they offer intensive instructional programs and are usually hosted by 2-year and 4-year colleges. The study found that: (1) Upward Bound has early positive impacts on students' educational expectations and academic course-taking; (2) students with lower educational expectations initially benefit more from Upward Bound; (3) Hispanic students initially benefit most from Upward Bound; and (4) many students (about 37 percent) who enter Upward Bound leave the program during the first year. After an executive summary and introductory chapter, Chapter 2 presents data on persistence in Upward Bound, and on the Upward Bound services offered. Chapter 3 details short-term impacts of Upward Bound, including the average impact of the program and groups benefitting most. The concluding chapter summarizes findings, compares them to previous findings, and draws implications for program improvement. Eight appendices provide additional detail on research methodology, data interpretation, and statistics. (Contains 18 references.) (DB)
Sponsoring Agency: Department of Education, Washington, DC. Office of the Under Secretary.
Contract Number: LC-92001001.
ERIC Note: For other reports in this series, see HE 030 836-838.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Aspiration; Access to Education; College Bound Students; Compensatory Education; Disadvantaged Youth; Dropout Rate; Economically Disadvantaged; High Schools; Higher Education; Hispanic Americans; Longitudinal Studies; Minority Groups; Noncollege Bound Students; Partnerships in Education; Program Effectiveness; Student Educational Objectives; Upward Bound; Reports, Evaluative